2020
DOI: 10.1002/jcla.23295
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic values of preoperative platelet parameters in patients with gynecological tumors

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…The result of the 95% CI of AUC of PLT: 1.000-1.000 may be due to the small sample size of this study, and further evaluation is needed to increase the sample size. These results are consistent with the study byYang et al 20 .…”
Section: Discussionsupporting
confidence: 94%
“…The result of the 95% CI of AUC of PLT: 1.000-1.000 may be due to the small sample size of this study, and further evaluation is needed to increase the sample size. These results are consistent with the study byYang et al 20 .…”
Section: Discussionsupporting
confidence: 94%
“…The increase in neutrophil count is stimulated by inflammatory cytokines to promote neutrophil phagocytic and bactericidal effects, which provides the "fuel that feeds the flames" of tumor growth and metastasis (25,26). Several studies have confirmed the prognostic value of PLT count in lung cancer, gynecologic malignancies, melanoma, and hepatocellular carcinoma (27)(28)(29)(30)(31)(32). PLTs have been suggested to mediate antigen presentation by dendritic cells to T cells (33) and form heterotypic aggregates with neutrophils (34).…”
Section: Discussionmentioning
confidence: 99%
“…89 The argument that supports the roles attributed to platelets in ovarian carcinomas, especially in high-grade serous ones, is the result of published studies, which consistently identify, preoperatively, the presence of thrombocytosis. 38,90,92,93 The circulating platelet excess can be explained by the role of these acellular figured elements, as reactants of inflammation, the hyperproduction being induced by the pro-inflammatory cytokines: IL-1, IL-6, and IL-11. 40,94 The involvement of platelets in the process of carcinogenesis and associated inflammation results from the action they induce at the level of sphingolipids of cell membranes, represented mainly by ceramides (CER), glucosylceramide (GlcCer), sphingosine (SPH), and sphingosine-1-phosphate (S1P) 95 Selectively, cellular oxidative stress is a stimulating factor of sphingosine and/or ceramide synthesis, and among these, the distinctive role in modulating the process of development, progression, metastasis, and even in the chemoresistance of neoplasia, belongs to CER.…”
Section: The Relationship Between the Chronic Inflammatory Process An...mentioning
confidence: 99%